Hepatitis B seroprevalence in 10-25-year-olds in Mexico - the 2012 national health and nutrition survey (ENSANUT) results - Hugo López-Gatell; Lourdes García-García; Gabriela Echániz-Avilés; Pablo Cruz-Hervert; María Olamendi-Portugal; Deyanira Castañeda-Desales; Miguel Ángel Sanchez-Alemán; Martin Romero-Martínez; Rodrigo DeAntonio; Maria Yolanda Cervantes-Apolinar; Ricardo Cortes-Alcalá; Celia Alpuche-Aranda (Taylor & Francis Group, 2019)
Objectives: To estimate hepatitis B virus (HBV) seroprevalence from natural infection or vaccination in 10-25-year-olds in Mexico, using the 2012 National Health and Nutrition Survey (ENSANUT). Methods: Randomly selected serum samples (1,581) from adolescents and young adults, representative of 38,924,584 Mexicans, were analyzed to detect hepatitis B surface antigen (HBsAg), hepatitis B surface antibody (anti-HBs) and hepatitis B core antibody (anti-HBc). Weighted HBV seroprevalence in the Mexican population and association with sociodemographic variables were calculated. Results: Overall weighted seroprevalence from natural infection (positive for anti-HBs and anti-HBc) was 0.23% (95% confidence interval [95% CI] 0.10-0.52). No HBsAg was detected, indicating no acute or chronic infection. Vaccine-derived immunity (positive ≥ 10.0 mIU/ml for anti-HBs and negative to anti-HBc) was 44.7% (95% CI: 40.2-49.4) overall; lower in persons aged 20-25 years (40.83%) than in persons aged 10-19 years (47.7%). Among the population analyzed, 54.2% (95% CI: 49.6-58.8) were seronegative to HBV (negative for all three markers) and no sociodemographic risk factors were identified. Conclusions: HBV seroprevalence from natural infection was low. Vaccination-induced immunity was higher among Mexican adolescents than young adults, possibly due to vaccination policies since 1999.